Детермінанти впливу на економічний суверенітет у воєнний та повоєнний період - Єфремова, К. В. (НДІ ПЗІР НАПрН України, 2022)
Стаття присвячена питанням визначення екзогенних детермінант впливу на економічний суверенітет в особливий період. Авторка пропонує класифікацію таких чинників виходячи зі складових частин економічного суверенітету. Запропоновано розглядати систему детермінант впливу на економічний суверенітет не лише національного рівня, а перш за все зважаючи на дисбаланси, що виступають загрозою стабільності світового рівня, через регіональну та галузеву економічну взаємозалежність держав. У дослідженні деяким детермінантам, що впливають на фінансову самостійність держави, продовольчу самозабезпеченість та демографічну стабільність завжди, як у воєнний період, так і поза ним, приділено особливу увагу, зокрема, співпраця держави з міжнародними фінансовими установами, міграційні процеси працездатного населення та релокація бізнесу за межі країни. МВФ відіграє важливу роль у формуванні економічних політик країн-членів як головний наднаціональний орган регулювання міжнародних валютно-кредитних відносин та безпосередньо впливає на реалізацію державами свого економічного суверенітету. Авторка звертає увагу на те, що міжнародні заходи щодо фінансової підтримки України (фінансування колективного Заходу) на умовах довгострокового кредитування сприяє досягненню макроекономічної стабільності, своєчасному миттєвому відновленню інфраструктури та підтриманню конкурентоспроможності української економіки, однак не вирішує усі глибині проблеми та не знижує загальну суму державного боргу, що у майбутньому буде важелем впливу на економічний суверенітет країни. Зроблено висновок що, в Україні у воєнний період та деякий час після, відбуватиметься тимчасове обмеження реалізації економічного суверенітету, що вимагає від влади країни рішучих дій щодо розроблення зваженої економічної стратегії відновлення України для мінімізації впливу екзогенних детермінант впливу. Problem setting. The Russian invasion of Ukraine caused heavy casualties, significant displacement of the population, and extensive damage to infrastructure. The impact on economic activity is enormous: real GDP has fallen sharply, inflation has risen, trade has been significantly disrupted, and the budget deficit has risen to unprecedented levels. All this directly affected the realization of the economic sovereignty of Ukraine. Analysis of recent researches and publications. During the last decade, domestic authors devoted a lot of attention to the study of the legal nature of economic sovereignty and the factors influencing it. However, the works of E. M. Bilousov, I. V. Yakovyuk, O. B. Vasylchyshyn, A. Yu. Tkrenko, M. M. Khapatniukovskii, B. V. Derevyanka, and V. M. Kostyuchenko deserve special attention. At the same time, the problem of ensuring economic sovereignty in the conditions of martial law and in the post-war period is only raised in scientific research, which determines its relevance. The target of the research is to find out the significance of external determinants of influence on the processes of ensuring the economic sovereignty of Ukraine in a special period, as well as to substantiate the priority directions of the state’s economic policy to reduce the negative factors of influence on economic sovereignty in order to realize the national interests of post-war economic recovery. Article’s main body. The article is devoted to the issues of determining exogenous determinants of influence on economic sovereignty in a special period. The author proposes to consider the system of determinants of influence on economic sovereignty not only at the national level, but first of all, taking into account the imbalances that threaten the stability of the world level due to the regional and sectoral economic interdependence of states. The author offers a classification of such factors based on the constituent parts of economic sovereignty. In the study, special attention was paid to some determinants, in particular, the cooperation of the state with international financial institutions, the migration processes of the working population and the relocation of business outside the country. Conclusions and prospects for the development. The author draws attention to the fact that international measures for financial support of Ukraine (financing of the collective West) on the terms of long-term crediting contribute to the achievement of macroeconomic stability, timely and immediate restoration of infrastructure and support of the competitiveness of the Ukrainian economy, but do not solve all the deep problems and do not reduce the total amount of public debt , which in the future will be a lever of influence on the economic sovereignty of the country. It is concluded that, in Ukraine during the war period and for some time after, there will be a temporary limitation of the realization of economic sovereignty, which requires the country’s authorities to take decisive actions to develop a balanced economic strategy for the recovery of Ukraine in order to minimize the impact of exogenous determinants of influence.
Keywords: економічний суверенітет; економічна безпека держави; воєнний стан; міграційні процеси; релокація бізнесу; МВФ; ЄС; відновлення України; economic sovereignty; economic security of the state; martial law; migration processes; business relocation; IMF; EU; restoration of Ukraine